The impact of unproved reserve news on the energy stock volatility: an empirical investigation on Turkey - Arzova, Sabri Burak; Koy, Ayben; Sahin, Bertac Sakir (EMERALD GROUP PUBLISHING LTD, 2024)
PurposeThis study investigates the effect of unproven energy reserve news on the volatility of energy firms' stocks. Thus, investors' perception of unproven energy reserves is revealed. Additionally, the study aims to determine whether the effect of the news changes according to time and volatility level.Design/methodology/approachThe general autoregressive conditional heteroskedasticity (GARCH) and exponential generalized autoregressive conditional heteroskedasticity (EGARCH) models consist of the energy reserve exploration news in Turkey for the period 2009-2022 and the volatility of 14 energy stocks.FindingsThe results indicate energy exploration news's negative and significant effect on volatility. According to empirical results, energy stock volatility is most affected in the first ten days. Besides, the results show that the significant models of energy reserve news in low-volatility stocks are proportionally higher than in high-volatility stocks.Research limitations/implicationsOnly unproved reserve news is included in the analysis, as sufficient confirmed reserves could not be reached during the sampling period. Further studies can compare proven and unproved reserve news effects. Additionally, a similar analysis can be conducted between Turkey and another country with a similar socio-economic character to examine different investor behaviors.Practical implicationsThis research includes indications on managing investors' reactions to unproven energy reserve news.Originality/valueThis study contributes to the literature by analyzing unproven reserves. Contrary to previous studies, examining stock volatility also makes the study unique.
Keywords: Unproved energy reserves; Investor perception; Turkey; GARCH (1; 1); G40; G10 G11; C50; OIL PRICE SHOCKS; CLEAN ENERGY; BEHAVIORAL FINANCE; MACROECONOMIC NEWS; RETURNS; MARKETS; SECTOR; FIRMS; OVERCONFIDENCE; UNCERTAINTY; Business & Economics